Az elemzési egység és az ekvivalenciaskála megválasztásának hatása a jövedelmi egyenlőtlenségre és szegénységre (Szociológiai Szemle, 2024)
The authors present the theoretical bases and the results of an equivalence scale developed recently in the HSO. The paper shows how the income distribution and various measures of income inequality are affected by the choice of the equivalence scale. The authors investigate the impact of this choice on the phenomenon of poverty. According to the authors' opinion no global, generally applicable equivalence scale can be constructed because an appropriate scale is largely determined by the country's special circumstances. In order to change the present Hungarian practice they suggest not only professional, but also political consensus, because the choice of the equivalence scale can be advantageous for certain social groups, while disadvantageous for others.